2005
DOI: 10.2337/diabetes.54.5.1607
|View full text |Cite
|
Sign up to set email alerts
|

The +276 Polymorphism of the APM1 Gene, Plasma Adiponectin Concentration, and Cardiovascular Risk in Diabetic Men

Abstract: Recently, the genetic variability at adiponectin locus (APM1) was associated with cardiovascular risk in patients with type 2 diabetes. We sought to examine the associations of five variants of APM1 gene (C-11365G, A-4034C, A-3964G, T45G, and G276T) with the risk of cardiovascular diseases (CVDs) in a larger cohort of diabetic patients. Of 879 diabetic men from the Health Professionals Follow-up Study, 239 participants developed coronary heart disease or stroke during 14 years of follow-up and 640 CVD-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
90
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 21 publications
14
90
4
1
Order By: Relevance
“…4,[25][26][27] Decreased adiponectin levels were described in weight-stable obese subjects. However, many studies have reported an association between obesity risk and hyperadiponectinemia associated with polymorphisms, 9,18,28 which were in accordance with our results. The physiological mechanisms to explain these results are a complex question to address.…”
Section: Discussionsupporting
confidence: 93%
“…4,[25][26][27] Decreased adiponectin levels were described in weight-stable obese subjects. However, many studies have reported an association between obesity risk and hyperadiponectinemia associated with polymorphisms, 9,18,28 which were in accordance with our results. The physiological mechanisms to explain these results are a complex question to address.…”
Section: Discussionsupporting
confidence: 93%
“…Diabetic subjects showed that plasma adiponectin levels are significantly higher in TT homozygous T2DM patients, in accord to similar findings in the literature [36]. In addition other studies dealt with 276 G/T allele, it was found that T allele of this variant was related with higher levels of serum adiponectin and was a protective factor fordiabetes, coronary heart disease, hypertension, or dyslipidemia in American [37], Fenland [38], Japanese, and Korean [39] populations. However, the conclusions in different populations are somehow controversial.…”
Section: Discussionsupporting
confidence: 80%
“…However, SNP45T4G alone did not have any significant association. Furthermore, Qi et al 24 recently found significant associations between ADIPOQ SNP276G4T and increased plasma adiponectin levels and decreased cardiovascular risk in diabetic men. Taken together, a haplotype including SNPs À11391 and À11377 in the proximal region was found to be associated with the risk of type 2 diabetes in French Caucasian.…”
Section: Discussionmentioning
confidence: 97%